2022
DOI: 10.3390/jcm12010016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on Corneal Neuroimmune Features in Type 2 Diabetes

Abstract: Aim: To determine the impact of chronic kidney disease on corneal nerve measures and dendritic cell counts in type 2 diabetes. Methods: In vivo corneal confocal microscopy images were used to estimate corneal nerve parameters and compared in people with type 2 diabetes with chronic kidney disease (T2DM-CKD) (n = 29) and those with type 2 diabetes without chronic kidney disease (T2DM-no CKD) (n = 29), along with 30 healthy controls. Corneal dendritic cell densities were compared between people with T2DM-CKD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
2
5
0
Order By: Relevance
“…The current study sought to ascertain whether changes in corneal nerve parameters are associated with an alteration in tear film substance P concentration in people with type 2 diabetes with concurrent chronic kidney disease compared to people with type 2 diabetes alone. Even though we demonstrated that corneal nerve parameters were reduced in type 2 diabetes with concurrent chronic kidney disease, consistent with previous findings [ 3 ], we found no difference in tear film substance P concentration between the two diabetes groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current study sought to ascertain whether changes in corneal nerve parameters are associated with an alteration in tear film substance P concentration in people with type 2 diabetes with concurrent chronic kidney disease compared to people with type 2 diabetes alone. Even though we demonstrated that corneal nerve parameters were reduced in type 2 diabetes with concurrent chronic kidney disease, consistent with previous findings [ 3 ], we found no difference in tear film substance P concentration between the two diabetes groups.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown greater corneal nerve loss in diabetic chronic kidney disease compared to type 2 diabetes alone when the severity of peripheral neuropathy is matched between the two groups [ 3 ]. Tear film substance P is mainly expressed and released by corneal neurons and exerts its physiological effects through the neurokinin receptors on the ocular surface [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DM presents as a low-grade chronic in ammatory pathology. In ammation plays a pivotal role in the development and progression of diabetic eye disease (DED), in conjunction with increases in proin ammatory mediators, apoptosis, and vascular permeability (Asiedu et al 2022;Liu et al 2023). Current research on the link between in ammation and DED has focused on DR and DME.…”
Section: Introductionmentioning
confidence: 99%